Modelos de ensino público, eficiência e gestão escolar: uma análise da escola de ensino médio regular de Quixaba e da escola de ensino médio integral de Timbaúba, no estado de Pernambuco. - Silva, Valdemberg Dias da (2013)
The different school models pass through various evaluative mechanisms that put the test different models of management and education in the public schools. The search for qualitative models of public schools from quantitative evaluation mechanisms puts managers set goals for the insertion of their schools in the top ranking positions state wide and nationally. Pernambuco is no exception to search for satisfactory results in the evaluation processes of teaching quality and management. We observe empirically phenomenon referred to in the process that involves two models of secondary education in the state education system of Pernambuco, which is a regular state school and integral public school pointing performance relative to one another. From that point, we define our central question is: how to explain the performance of a regular school in opposite an integral school receives greater support from public and private management? In this sense, our objective is to develop a comparative study of the performance of a regular school and integral school in the State of Pernambuco, considering their spatial, social and economic. The methods of approach launched o forget unveiling of the question proposed above and the objective pursued, pass through the operationalization of qualitative and quantitative al yes is and the historical and dialectical materialism. Regarding the procedures and techniques, this research is defined by literature, field research and interviews. As results of this study, we consider how school management, even in regions with low HDI, shows satisfactory levels in relation to models of management schools focus for greater incentives, as noted in the school located in the Hinterland of Quixaba relative located in the Zone of Wood in Timbauba. The rigor of school activities associated with the increased presence of family provides higher performance n the evaluation processes considered in this study. We conclude that not enough young to have a life almost in the integral school, but the performance goes through greater investment in training and skills, discipline and school interaction with family, no matter the region and the social and economic conditions.